2000
DOI: 10.1037/0003-066x.55.10.1160
|View full text |Cite
|
Sign up to set email alerts
|

Who is rich? Who is happy?

Abstract: esteem, again I would like to offer an alternative explanation, namely, that self-esteem is normal in nonsmokers but impaired in smokers (as it is in many forms of drug dependency). Smokers who are quitting the habit should therefore experience a range of psychobiological improvements. This leads to another point: Not only does nicotine dependency cause stress (Parrott, 1999), it also leads to greater depression (Parrott, 2000a) and probably many other problems. Yet, there is surprisingly little research into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 6 publications
1
18
0
Order By: Relevance
“…Good provider/public sphereSocioeconomic status (SES) has been associated with subjective well-being and mental health (Belle, Doucet, Harris, Miller, & Tan, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…Good provider/public sphereSocioeconomic status (SES) has been associated with subjective well-being and mental health (Belle, Doucet, Harris, Miller, & Tan, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…Clarifying the association between father involvement and adolescent mothers' psychological adjustment is important for several reasons. As stated above, research has found high rates of depression among low-income, minority mothers (e.g., Belle, Doucet, Harris, Miller, & Tan, 2000). Maternal stress and depression can take a toll on young mothers' parenting skills; depressed adolescent mothers have been rated as less competent in their parenting of infants than their nondepressed counterparts (Gelfand, Teti, & Fox, 1992).…”
Section: Father Involvementmentioning
confidence: 97%
“…8,No.2, 2008 likely to accept complete dentures, than with the low levels. (20,21) If a comparison was done only for the completely edentulous groups, the result showed that the group with an age between fifty five and sixty four years of old that received treatment at Dentistry College at Mosul University, had the highest score within Mental Health Scale= 81.329, Table (4). This was also similar to investigations done by Hagglin et al (22) , and the opinion for such result that person at this age become a mature and wise mentally than other ages.…”
Section: Resultsmentioning
confidence: 99%